Inkjet-Printed Interdigital Bandpass Filter with Wide Stopband Using Multilayer Liquid Crystal Polymer Technique - Li-Chun Chang; Cheng-Lin Cho; Sameer Kamrudin Bachani; Hsuan-Ling Kao (International Journal of Antennas and Propagation)
This article presents a two-layer inkjet-printed interdigital bandpass filter using lamination bonding process on liquid crystal polymer (LCP) substrates for radio frequency electronic applications. Various percentages of torque force were applied over a 4 × 4 cm2 area with a 942 kg fixed force in the lamination bonding process. The insertion loss and surface morphology of the inkjet-printed silver film were examined on various torque forces to develop the lamination bonding process. The lamination bonding was performed at 12% torque and 270°C. A three-dimensional bandpass filter was realized with a S21 of −2.2 dB at 11.5 GHz with a 17% fractional bandwidth. A multilayer inkjet-printed bandpass filter was successfully developed to verify the design methodology and fabrication of inkjet-printing technology and lamination bonding technique for a three-dimensional integrated circuit package.